The relationship between the superior frontal cortex and alpha oscillation in a flanker task: Simultaneous recording of electroencephalogram (EEG) and near infrared spectroscopy (NIRS). (June 2018) - Suzuki, Kota; Okumura, Yasuko; Kita, Yosuke; Oi, Yuhei; Shinoda, Haruo; Inagaki, Masumi
Highlights: Larger SFC activity was related to alpha enhancement in the occasional condition. SFC activity was not correlated with alpha activity in the successive condition. Information flow of alpha2 was not directed in the successive condition. Abstract: Activity in the alpha band of the electroencephalogram (EEG) reflects functional inhibition of the cerebral cortex. The superior frontal cortex (SFC) is known to control alpha activity. Based on this relationship between SFC and alpha, we hypothesized that SFC controlled alpha mediates proactive control over interference. In this study, we examined the relationship between SFC and alpha in the flanker task by simultaneously recording EEG and near infrared spectroscopy (NIRS). Forty participants performed a flanker task with occasional (compatible 75%, incompatible 25%) and successive (incompatible 100%) conditions. In the occasional condition, larger SFC activity was related to pre-stimulus alpha enhancement under occipital electrodes. This is consistent with a model in which SFC enhances pre-stimulus alpha activity, leading to proactive control over interference. However, we could not detect a correlation between SFC activity and alpha activity in the successive condition. Active inhibition may have been reduced by a need to continuously inhibit brain regions associated with the irrelevant information. This may have reduced the role of the SFC in controlling alpha activity. Based on these findings, we postulate that there are two cerebral mechanisms of proactive control over interference.